Correction: Silva et al. Abnormal Neurologic and Motor Function in Newborns Treated for Congenital Syphilis. Infect. Dis. Rep. 2025, 17, 34 - Bruna Silva; Luciana Friedrich; Graziela Biazus; Renata Bueno; Carla Almeida (Infectious Disease Reports, 2025)
In the original publication [...]